The Effect of Curing Time on The Mechanical Properties of Polystern Reinforced Alumina Particular Composite - Mohammed, Ali Hussein (Nahrain University College of Engineering Journal, 2012)
The goal of the present research was to study the effect of curing time on the mechanical properties of particular composite. Of critical importance was the capability to predict resin flow and compaction during cure. Such a model could be used to determine optimum cure cycles without a need for experimental trial and error.The experimental work includes steps .The first step is mixing the polyester with the Alumina powder with particular size ranged from 25 to 36 ?m with different weight ratios (0, 10, 20, and 30%) and the second steps is putting it in the heater furnace at 70oC at different curing time (1, 2 and 3 hours) to known the properties acquired and the third step is tested in the tensile test for all specimens. The conclusion of this test is summarized that the curing time of the presented composite is about 2 hour with 70oC.